Experimentation on the human embryo: a new requirement of science and medicine? - Serra, Angelo (Medicina e Morale, 1993)
The reproductive technologies, which at the beginning were aimed at overcoming couples' sterility, have actually becorne a preferential opportunity to obtain "human material" to experiment on. The spare embryos, or those obtained with specific in vitro fertilization, can be used in cellular biology, molecular genetics, cytogenetics and biochemistry studies. In this article, the Author, after an accurate analysis of the present situation, evaluates wheter it's necessary to use human embryos in experiments, considering the fact that, because they have been human individuals since their fertilization, they require the same respect as the person who is already born.